Morbidity and psychological impact of prostate biopsy: the future calls for a change - Andrea Minervini; Gianni Vittori; Giampaolo Siena; Marco Carini (Asian Journal of Andrology, 2014)
Currently transrectal ultrasound-guided prostate biopsy (TRUS-Bx) is one of the most common urological procedures, with more than 1 million performed per year in Europe and the United States. [1] Among patients undergoing TRUS-Bx, approximately one-third will receive a diagnosis of prostate cancer (PCa), while two-thirds receive a negative result on initial biopsy. Negative biopsy patients maintain an estimated risk of repeated biopsy of 12% at 1 year and 38% at 5 years. [2] Standard TRUS-Bx is likely to systematically miss significant tumors, particularly in the anterior and apical parts of the gland. [3] A crucial aim of urologists in the next decade is to increase the accuracy of the procedure and avoid the use of inappropriate biopsies.